2018
DOI: 10.1002/htj.21330
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prandtl number on the average exit temperature of coolant in a heat‐generating vertical parallel plate channel: A conjugate analysis

Abstract: A coupled conduction–convection heat transfer analysis is carried out for a two‐dimensional rectangular, vertical parallel plate channel producing volumetric energy (uniform and nonuniform), subjected to laminar forced‐convection incompressible fluid flow under steady‐state conditions. The equations governing the thermal and flow field are solved by using finite difference method, and the resulting algebraic equations are solved by using the tridiagonal matrix algorithm method. Four coolants with their Prandtl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The above non-dimensionalized parameters are selected based on previous research work that are close to conjugate study of parallel plate channel (Kaladgi et al 2019;Abdul Razak et al 2019;Mohamme Samee et al 2019;Samee et al 2018).…”
Section: Numerical Methodologymentioning
confidence: 99%
“…The above non-dimensionalized parameters are selected based on previous research work that are close to conjugate study of parallel plate channel (Kaladgi et al 2019;Abdul Razak et al 2019;Mohamme Samee et al 2019;Samee et al 2018).…”
Section: Numerical Methodologymentioning
confidence: 99%
“…Apart from this there are many studies available which speaks about the behavior of vertical parallel plates subjected to flow of fluid under forced and mixed convection flow regime [19][20][21][22][23]. Recently Samee et al have investigated numerically about effect of Prandtl number on coolant exit temperature flowing through the heat generating parallel plate channel and Li-ion battery cells [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Numerical studies reported by the Ramis et al were associated with single heat generating plate subjected to forced convection flow of coolant under conjugate, laminar, incompressible flow condition [3,4]. Whereas the study reported by Samee et al is pertinent to heat generating parallel plates but considered only the effect of Prandtl number on exit temperature of coolants [24].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of heat‐transfer coefficient between coolant and fuel rod on the temperature histories of the fuel pellet and the cladding was also inspected. Similarly, a number of studies are available in the literature that has considered the analysis of 2D plates/fins/fuel elements with or without uniform heat generation along with steady or transient heat‐transfer criteria …”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a number of studies are available in the literature that has considered the analysis of 2D plates/fins/fuel elements with or without uniform heat generation along with steady or transient heat-transfer criteria. [20][21][22][23][24][25][26][27][28][29][30] With the exception of Ramis et al, [6][7][8]16 most of the researchers have solved the 1D heat conduction equation to find the temperature distribution in the nuclear fuel element. In most of the studies, the conjugate effect of heat transfer and realistic nonuniform heat generation was not considered.…”
mentioning
confidence: 99%